Investigating the Students’ Views on the Authentic Materials Used in Basic Speaking Class - Hartatik, Sri Fatmaning; Rahmah, Tities Hijratur (Universitas Islam Negeri Sultan Aji Muhammad Idris Samarinda, 2016)
This current study was intended to investigate the student point of views on the use of authentic materials (AMs) used in the process of teaching and learning speaking at the first semester in English Department, IKIP Budi Utomo Malang. A descriptive qualitative was employed to portray the intended data. The data were revealed from 22 students experiencing learning speaking by using authentic materials (AMs). To help the researcher, as the key instrument, to obtain the data, the researcher used an interview guide. To make the data display clear, the findings were classified into three classes; they were students’ views on the use of videos, student’ views on dialogues used in Basic Speaking, and students’s point of views on the pictures used as Ams. In general, the interview results showed that AMs were basically interesting, motivating, providing information on how the language used and how English culture is, raising students’ feeling of confidence. In term of the comprehensibility of the materials, however, only a few students stated that the presented materials were understandable; while the others thought that they could not understand the AMs because the spoken communication made by native speakers was too fast. Based on the findings, it can be concluded that the teaching material presented in the Basic Speaking class viewed in positive manners by the students. Some students, however, found that the materials, especially conversation made by native speakers, were seen incomprehensible as the models in the video spoke too fast and used long sentences. This informed the teachers that even though AMs were found to be beneficial, AMs should be carefully selected; by so doing, it is expected that the AMs will opt to the students’ level.